The Rural Enterprise Project (REP): phase ending report on October 1985 to June 1989 - BRAC (© BRAC, 2016)
1. Introduction 2. REP: an overview 3. Work methodology & project status 3. Materials development & training 4. Consultation, technical assistance & foreign tour 5. Summary of REP phase: evaluation 6. Conclusion.